Continuous biodiesel production with anion-exchange resin / Takuya Ito ... [et al.] - Ito, Takuya; Kakuta, Yusuke; Hirano, Katsumi; Suganuma, Hideki; Kato, Shigeru; Suzuki, Seiichi; Kojima, Toshinori (Universiti Teknologi MARA, Pulau Pinang, 2015)
Biodiesel attracts attention as an alternative to fossil fuel. Though the raw material of biodiesel is renewable and carbon neutral, in the conventional method the product is contaminated with the homogeneous alkali catalyst. Hence, the application of the anion-exchange resin was used as the solid base catalyst. While the method of using the anion-exchange resin has already been reported, a problem in durability remains. In the present paper, the reaction mechanism of the transesterification using the anion-exchange resin was examined. As a result, it was suggested that the ion exchange between the hydroxyl ion of the resin and the methoxide ion of the methanol occurred first in the transesterification when the anion-exchange resin was used. The fatty acid was generated by hydrolysis of triglyceride because the water was generated along with this ion exchange reaction. Then, the methoxide type anion-exchange resin without hydroxyl group was made as starting material for experiments. The applicability of the methoxide type anion-exchange resin to the fixed bed reactor in the biodiesel manufacturing process was examined. As a result, its applicability was confirmed by using a part of producing biodiesel as the recycling solvent and by adding excessive methanol.